Numerical modeling of inviscid acoustic waves in a closed chamber - T. C., Mah (2007)
The mathematical sciences is a subject of key global importance, underpinning developments in most areas of science and technology. The growing concern on the transfer of mathematical sciences knowledge demands the enhancement in the competency of this discipline. Applying mathematical sciences to challenging problems of the real world has made the field bustling with excitement and satisfaction. Thus, it is with great pleasure for the School of Mathematical Sciences to present the 4th International Conference on Mathematical Sciences, ICMS4 2016, to further bridge as well as nurture the understanding and collaboration amongst the regional and global mathematical scientists and practitioners.